Fog-like fluffy structured N-doped carbon with a superior oxygen reduction reaction performance to a commercial Pt/C catalyst1. Issue 8 (28th February 2015) - You, Chenghang; Zen, Xiaoyuan; Qiao, Xiaochang; Liu, Fangfang; Shu, Ting; Du, Li; Zeng, Jianhuang; Liao, Shijun
<x xml:space="preserve">Abstract</x> A high-performance N-doped carbon catalyst with a fog-like, fluffy structure was prepared. The catalyst exhibits superior ORR performance to commercial Pt/C catalyst in alkaline medium.